Assessing Nigrostriatal Dopaminergic Pathways via 123I-FP-CIT SPECT in Dementia With Lewy Bodies in a Psychiatric Patient Cohort - Hansen, Niels; Lange, Claudia; Timäus, Charles; Wiltfang, Jens; Bouter, Caroline (Frontiers in Aging Neuroscience, 2021)
Background (123)-I-2-ß-carbomethoxy-3ß-(4-iodophenyl)-N-(3-fluoropropyl) nortro- pane single photon emission computed tomography (123I-FP-CIT SPECT) was validated to distinguish Alzheimer’s dementia from dementia with Lewy Bodies (DLB) by European medical agencies. Little evidence exists that validates 123 I-FP-CIT SPECT as a supplementary method to diagnose probable DLB in a psychiatric cohort of patients with psychiatric symptomatology and suspected DLB. We aim to elucidate differences in the clinical phenotype of DLB between those patients with and those without a positive 123 I-FP-CIT SPECT indicating a nigrostriatal deficit. Methods To investigate this, we included 67 patients from the Department of Psychiatry and Psychotherapy at University Medical Center Göttingen (UMG) in our study who had undergone 123I-FP-CIT SPECT in the Department of Nuclear Medicine (UMG) by evaluating their patient files. Results 55% with a positive-123I-FP-CIT SPECT and probable DLB after the 123I-FP-CIT SPECT exhibited psychiatric features. The number of probable DLB patients in those exhibiting psychiatric symptoms was higher post-123I-FP-CIT SPECT than pre-123I-FP-CIT SPECT assessed cross-sectionally over a 6-year period (p < 0.05). In addition, prodromal DLB and prodromal DLB patients with a psychiatric-phenotype yielded higher numbers post-123I-FP-CIT SPECT than pre-123I-FP-CIT SPECT (p < 0.05). Furthermore, we discovered no phenotypical differences between those DLB patients with a positive and those with a negative 123I-FP-CIT SPECT. 123I-FP-CIT SPECT-positive DLB patients in our psychiatric cohort revealed a psychiatric onset more often (52%); DLB was less often characterized by an MCI onset (26%) (p < 0.005). Conclusions Our findings support 123I-FP-CIT SPECT as an adjuvant tool for improving the diagnosis of probable DLB and prodromal DLB in a cohort of psychiatric patients with often concomitant psychiatric symptomatology. The psychiatric-onset is more frequent than an MCI-onset in DLB patients presenting nigrostriatal dysfunction, giving us an indication of the relevance of deep clinical phenotyping in memory clinics that includes the assessment of psychopathology.